The effect of the school meal program on knowledge, attitudes, and practices of balance nutrition among adolescent girls - Zahida Azmi Zaqia Zulfani; Ikeu Tanziha; Hadi Riyadi (AcTion: Aceh Nutrition Journal, 2026)
Anemia among adolescent girls remains a public health concern in Indonesia and is linked to low dietary diversity and inadequate nutrient intake. Despite existing school meal programs, evidence of their effects without formal nutrition education remains limited. This study aimed to evaluate the impact of a school meal program on knowledge, attitudes, and practices (KAP) related to balanced nutrition, anemia, and hygiene among female students. A quasi-experimental one-group pre–post test design was conducted with 80 grade-10 students at the State Vocational High School 1 Bogor, selected purposively during a four-week period from July to August 2025. KAP scores were collected using validated questionnaires and analyzed using the Wilcoxon test. The results showed a significant increase in knowledge (mean score 6,0 to 7.0; p= 0,043) and attitudes (median 8,0 to 10,0; p= 0,020) after one month of intervention, while practices remained unchanged (mean score 24,0 to 24,0; p= 0,371). Exposure to school meals and external nutritional information, particularly from social media, likely contributed to the improvement in knowledge and attitudes. However, unchanged practices may be due to short intervention duration, low household income, and limited access to diverse healthy foods. In conclusion, these findings highlight that free school meals can enhance knowledge and attitudes even without direct education; however, sustained behavioral change requires longer interventions, supportive environments, and parental involvement